Dual-tracer PET/CT imaging to determine tumor heterogeneity in a patient with metastatic ACTH-secreting neuroendocrine neoplasm: A case report and literature review - Ryzhkova, Daria; Mitrofanova, Lubov; Tsoy, Uliana; Grineva, Elena; Schlyakhto, Evgeny (Frontiers in Endocrinology, 2022)
Introduction We present a case of a patient with disseminated ACTH-secreting neuroendocrine neoplasm with biologic heterogeneity between a primary tumor and metastases. The diagnosis was obtained and multidisciplinary management was conducted with a positron emission tomography/computed tomography (PET/CT) scan with Gallium-68 [68Ga]-labeled dodecanetetraacetic acid-tyrosine-3-octreotate ([68Ga]-DOTA-TATE) and Fluor-18 [18F]-fluorodeoxyglucose ([18F]-FDG). Case report A PET/CT scan revealed a difference between [68Ga]-DOTA-TATE and [18F]-FDG uptake in primary tumor and several metastases. PET/CT showed high [18F]-FDG uptake and lack of [68Ga]-DOTA-TATE in the primary tumor, whereas both [68Ga]-DOTA-TATE and [18F]-FDG hyperaccumulation were identified in the majority of metastases. Despite positive [68Ga]-DOTA-TATE PET/CT, which is associated with high affinity with the somatostatin receptor 2 subtype, immunohistochemical examination revealed overexpression of the somatostatin receptor 5 subtype only. Perhaps, this explained the ineffectiveness of the treatment with “cold” somatostatin analogs. Conclusion This case had an aggressive clinical course, despite cytoreductive surgical treatment and somatostatin analog therapy. PET/CT imaging with two tracers is a molecular tool that demonstrates a biologic heterogeneity between a primary tumor and metastases and yields additional information that may influence the choice of the patient management strategy.